Community Knowledge and Behavior Towards Unwanted Pregnancy in Eight Provinces of Sumatra: Between Religious, Customary and State Norms - Lumbantobing, Dina; Bemmelen, Sita Van; Pratiwi, Andi Misbahul; Dhewy, Anita (Yayasan Jurnal Perempuan, 2019)
Based on field observations and experiences in assisting women by the PERMAMPU Consortium, there are still many women who face unwanted pregnancy (KTD). Therefore it is needed research to find out the needs of women related to KTD. This article focuses on three things, namely (1) understanding and knowledge of informants about KTD; (2) perception of the best and the worst solutions for KTD cases; (3) womenâ€™s behavior related to KTD. The study uses three categories of KTD: KTD experienced by married women, KTD experienced by unmarried women, and KTD experienced by victims of acts of violence. This article is written from the 2014 PERMAMPU Consortium research report entitled The Compilation of Unwanted Pregnancy Research Reports/KTD in Eight Provinces, Sumatra Island. The study used a qualitative approach with data collection conducted through interviews and FGDs. This paper shows that there are similarities and differences in the understanding, perceptions, behavior of women and society in relation to KTD. Various forms of rules and norms generally view pregnancy as natural, so that it is always desirable, have controlled women and society in behaving and handling KTD. There are various forms of KTD and various forms of coping methods that are not always in line with existing rules and are generally done secretly. Thus, women who experience unwanted pregnancy need recognition of their problems, including their voices and needs and supported to make decisions for themselves. Â